Childbirth as a metaphor for crisis: evidence from the ancient Near East, the Hebrew Bible and 1QH XI,1 - 18 - Bergmann, Claudia D. (Beihefte zur Zeitschrift für die alttestamentliche Wissenschaft, 2008)
Introduction -- The scope of this book -- Definitions of metaphor -- The approach to metaphor in this book -- Birth as event and metaphor in the ancient Near East -- The sources -- The experience of birth -- The experience of birth becomes a metaphor -- Birth as event and metaphor in the Hebrew Bible -- Birth as an event in the Hebrew Bible -- Birth as a metaphor in the Bebrew Bible -- The biblical birth metaphor for cases of local crisis -- War imagery and bad news -- War imagery -- Divine punishment imagery -- The biblical birth metaphor for cases of universal crisis -- Texts -- The biblical birth metaphor for cases of personal crisis -- Engulfment imagery -- War imagery -- Prophetic vision imagery -- 1QH XI, 1-18: the birth metaphor at Qumran -- 1QH XI, 1-18 within the corpus of the Hodayot -- The identity of the mothers and the children in 1QH XI, 1-18 -- Interpreting 1QG XI, 1-18 in light of the birth metaphor -- 1QH XI, 1-18 : personal and universal crisis